Olle in ceramica grezza con marchio: nuovi dati per l’analisi interpretativa - Mazzocchin, Stefania (Rei Cretariae Romanae Fautorum Acta, 2023)
A specific coarse-ware pot, as Gambacurta 54b, with a stamp on the wall has been identified. The first research, carried out 25 years ago, identified a small number of stamps, all concentrated in Patavium. Today there are 65 stamps, in Patavium and in its territory, and in a wider area. The epigraphic study let us to know some onomastic indications, often cryptic. The stamped pots are dated between the 2nd century BC and the early Roman period. The aim of this new research, moving from recent urban discoveries, is the analysis of new stamps, the excavations contexts, the pot typology and circulation; proposing new ideas on the stamps’ meaning in connection with a possible content.